Imaging precursory cluster fluctuations in ferroelectrics with pump-probe speckle spectroscopy - Ji, Kai (Phase transitions, 2011)
We report an investigation on the dynamic property of a photo-created ferroelectric cluster observed in the paraelectric BaTiO 3 as a real time correlation of speckle pattern between two soft X-ray laser pulses, at just above the paraelectric-ferroelectric phase transition temperature. Based on a model with coupled soft X-ray photon and ferroelectric phonon mode, we study the time dependence of scattering probability using a perturbative expansion approach. The cluster-associated phonon softening as well as central peak effects are reproduced well in the phonon spectral function via quantum Monte Carlo simulation. Also, it is found that the time dependence of speckle correlation is determined by the relaxation dynamics of ferroelectric clusters. Near the transition point the cluster excitation is stable, leading to a long relaxation time. While, at high temperature, the cluster structure is subject to thermal fluctuation, ending up with a short relaxation time.